Use of mild therapeutic hypothermia as a part of interventional therapy of patients with cardiac arrest due to acute coronary syndrome - Trąbka-Zawicki, Aleksander (2017)
In the group of patients admitted for interventional management of acute coronary syndrome complicated with cardiac arrest, significant inhibition of platelet activity in response to ticagrelor - a novel P2Y12 receptor inhibitor - has been documented in mild therapeutic hypothermia (MTH) conditions (32-34 degrees Celsius). The degree of platelet activity inhibition in this group was similar to the control group - conscious acute coronary syndrome patients treated interventionally in normothermic condition.Clinical efficiency of dual antiplatelet therapy (DAPT), consisting of ticagrelor, a novel oral P2Y12 receptor inhibitor, in combination with acetylsalicylic acid, as a therapy supportive to PCI in MTH conditions in out-of-hospital cardiac arrest (OHCA) patients, defined as freedom from thromboembolic events, has been confirmed. However, increased numbers of severe bleeding complications was observed in this group, what required intensive care unit (ICU) monitoring and blood transfusion therapy.Further clinical course and neurological condition in this group was favourable and dependent on cardiac arrest mechanism, occurrence and timing of early cardiopulmonary resuscitation, time to return of spontaneous circulation, lack of shock and renal failure, and, independently, on e
Keywords: acute coronary syndrome; cardiac arrest; therapeutic hypothermia